2022
DOI: 10.1111/zsc.12568
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide SNPs confirm plumage polymorphism and hybridisation within a Cyornis flycatcher species complex

Abstract: Morphology has been a leading taxonomic guiding light to systematists for the last couple of hundred years. However, the genetic and – more recently – genomic revolution have produced numerous demonstrations of erroneous classifications that were based on labile morphological traits. We used thousands of genome‐wide markers to shed light on evolutionary dynamics in a confusing and taxonomically obscure group of Asian Cyornis flycatchers. Using genomic data, we corroborated recent findings based on three mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Traditional morphology cannot be discarded or replaced by molecular technology for the classification of species. However, molecular genetic analysis can be a powerful auxiliary tool when morphological characteristics cannot provide a clear taxonomic determination (Davis et al., 2023; Ng et al., 2023; Paz‐Sedano, Alvarez, Gosliner, & Pola, 2022; Ronque, Azevedo‐Silva, Mori, Souza, & Oliveira, 2016; Ward & Blaimer, 2022). Within the phylogenetic tree we developed, L. yarkandensis and L. timidus clustered separately and distinctly from those in the other groups (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional morphology cannot be discarded or replaced by molecular technology for the classification of species. However, molecular genetic analysis can be a powerful auxiliary tool when morphological characteristics cannot provide a clear taxonomic determination (Davis et al., 2023; Ng et al., 2023; Paz‐Sedano, Alvarez, Gosliner, & Pola, 2022; Ronque, Azevedo‐Silva, Mori, Souza, & Oliveira, 2016; Ward & Blaimer, 2022). Within the phylogenetic tree we developed, L. yarkandensis and L. timidus clustered separately and distinctly from those in the other groups (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found a large number of hybridizations and gene introgressions between hares, especially between L. timidus and other hare species such as Lepus europaeus , Lepus granatensis , Lepus corsicanus and Lepus castroviejoi (Alves et al., 2003, 2006; Alves, Melo‐Ferreira, Freitas, & Boursot, 2008; Fernando et al., 2018; Ferreira et al., 2021; Liu et al., 2011; Melo‐Ferreira et al., 2005, 2012; Melo‐Ferreira, Alves, Freitas, Ferrand, & Boursot, 2009; Thulin, Fang, & Averianov, 2006; Thulin, Jaarola, & Tegelstrom, 1997; Thulin, Stone, Tegelstrǒm, & Walker, 2006). In terms of morphology, hybrid individuals can show very similar morphological characteristics to non‐hybrids, resulting in ambiguous classifications (Giska et al., 2019; Liu et al., 2011; Ng et al., 2023; Wang, 2017). In terms of genes, introgression and even genetic variation affect the origin and adaptation of organisms (Doebeli & Dieckmann, 2003; Seehausen, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…DNA extractions were performed using the DNeasy Blood & Tissue Kit (QIAGEN, Hilden, Germany) following the manufacturer's protocol for tissue. We prepared two libraries following Ng et al's [47] double-digest restriction-associated DNA sequencing (ddRADseq) protocol using EcoRI and MspI. To select for 250-600 bp fragments, as well as for the clean-up steps, we used Sera-Mag magnetic beads (Thermo Scientific, Waltham, MA, USA).…”
Section: Dna Extraction and Ddrad-seq Library Preparationmentioning
confidence: 99%
“…Numerous studies in the past two decades sought to infer the phylogenetic relationships for subsets of the Muscicapidae family (e.g., Roy et al, 2001;Beresford, 2003;Cibois and Cracraft, 2004;Outlaw and Voelker, 2006;Outlaw et al, 2007;Illera et al, 2008;Lim et al, 2010;Outlaw et al, 2010;Sangster et al, 2010;Zuccon and Ericson, 2010a;Zuccon and Ericson, 2010b;Aliabadian et al, 2012;Voelker et al, 2016Voelker et al, , 2012Barve and Mason, 2015;Moyle et al, 2015;Hooper et al, 2016;Zhang et al, 2016;Zhao et al, 2017;Alström et al, 2018;Fjeldså et al, 2020;Ng et al, 2022;Wei et al, 2022). Molecular phylogenetic studies revealed that the so called "flycatchers", "robins", and "chats" are not reciprocally monophyletic groups.…”
Section: Introductionmentioning
confidence: 99%